Stigmatization of Mental Health Issues in Children and Adolescents among Their Family in Eradah Complex and Mental Health-Dammam 2024 - Afrah Nouh Alzainaldeen,; Amerah Alzainaldain,; Norah Obeid Alsharif,; Abeer Abdulrahman Alabdulhadi,; Ebtsam Mhammed Shaban Tlete,; Khadijah Salman Salman al Khalifah,; Mona Saeed Alnakhlawi,; Nusrain Bader Sunbel,; Salma Muhammad alaali,; Jalilah Omran Alshulah,; Ahmed Abdal Hamid Al-Aufi, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background:The stigma surrounding mental health issues in children and adolescents is a critical concern, especially in settings like hospitals, mental health complexes, or institutions providing specialized care. In 2024, focusing on the stigmatization of mental health issues among families in institutions like Eradah Complex and Mental Health-Dammam offers valuable insights into how families, a key social support system, respond to mental health challenges faced by their children and adolescents. The study aims: To describe and relate attitudes toward mental health in children and adolescents along with myths associated with suicide in this population, familiarity with mental health, and potential professional help-seeking. Method: A cross-sectional study was used in a sample (N = 268). Socio-demographic variables, stigma associated with mental health problems in childhood and adolescence, myths about suicide, familiarity with mental health, and seeking professional help were assessed. Descriptive analyses mean difference and regression models were carried out. Results: The results reveal medium levels of stigma, the presence of myths about suicide and average familiarity with mental health. Mothers were a higher level of education, showed lower levels of stigma and fewer myths about suicide. A regression model explains the 44% of the variance with myths about suicide, stigma and familiarity with mental health as predictors of seeking professional help attitudes. Conclusions: Stigma, myths close suicide, and parental unfamiliarity with mental health may act as obstacles to appropriate diagnosis and treatment. Practical implications and recommendations are discussed.